Genetic and non-genetic analysis for milk production and reproductive traits in Holstein cattle in Egypt - E, Faid-Allah (Indonesian Animal Sciences Society, 2015)
This study was carried out to investigate genetic, non-genetic affecting factors and estimate genetic parameters for milk production and reproductive traits of Holstein cows via animal model. The data was obtained from a commercial farm (Safi Masr for Developing the Animal Resources), located in the Nile Delta, Dakahlia, Egypt. Data included 4791 records of 1797 cows, 794 dams and 67 sires that represented the period from 2002 to 2012. The means and coefficient of variability (CV%) of milk traits as total milk yield (TMY), 305 day milk yield (305-dMY), lactation period (LP) and dry period (DP) were 5787.8 kg (31.1%), 4695 kg (22.1%),Â 332 day (14.9%) and 72.3 day (27.7%), respectively. Also, the means (CV%) of reproductive traits as days open (DO) and age at first calving (AFC) were 157.9 day (22.6%) and 30.5 month (16.8%), respectively. Sire, dam, parity of cow, year and season of calving had significant effects on traits studied. Heritability estimated were 0.223, 0.184, 0.112, 0.118, 0.105 and 0.285 for TMY, 305-dMY, LP, DP, DO and AFC, respectively. Estimated rG and rP among milk production traits were positive but it takes negative trend with DP and DO. Moderate heritability estimates and positive genetic correlation for most of traits studied suggested that genetic improvement of these traits would be achieved via multi-trait selection. Key Words: Genetic Parameters, Milk Production, Reproductive, Friesian Holstein Cattle